Human detection and tracking using camera (Part II) - Chakravarthi, M. Rubern (2017)
In this project, the author learnt about human detection and tracking using OpenCV, Python and MATLAB. The author implemented solutions in Python using OpenCV to handle computer vision tasks such as face tracking, motion detection and tracking as well as human detection and tracking. The author also tested the feasibility of using the Raspberry Pi as platform for computer vision tasks.